Microalgas para fins alimentares: ênfase em compostos bioativos e saúde humana - Nascimento, Tatiele Casagrande do (2021)
In recent years, a trend has been established to explore food sources with capabilities beyond essential nutrition. In this sense, microalgal biomass has become a promising alternative since it is composed of several metabolites that can have beneficial effects on human health. Among the microalgae studied, the Scenedesmus genus is little explored in health, although it has an attractive biochemical profile. Given this, the objective of this work was to explore the influence of biomass intake and Scenedesmus obliquus carotenoid extract in experimental models in vivo, as well as to determine the bioaccessibility of carotenoids from this biomass in order to guide the best way of use. As a result, five articles and two book chapters (published or in the publication process) were generated, which were organized in this document into chapters. Chapters 1 to 5 refer to articles, and 6 and 7 refer to book contributions. Chapter 1: "Microalgae and health: a brief review" (review article in the process of publication); Chapter 2: "Exploratory data of the microalgae compounds for food purposes" (research article/publication completed); Chapter 3: "Microalgae biomass intake positively modulates serum lipid profile and antioxidant status" (completed publication); Chapter 4: "Microalgae carotenoids" intake: influence on cholesterol levels, lipid peroxidation and antioxidant enzymes" (research article/publication completed); Chapter 5: "Bioaccessibility and intestinal uptake of carotenoids from microalgae Scenedesmus obliquus" (research article/publication completed); Chapter 6: "Analytical protocols in antioxidant capacity measurement" (book chapter published); Chapter 7: "Biological properties of microalgae-based products" (book chapter scheduled for publication in December). Finally, the results of these scientific productions indicate that microalgae can be considered biosources of compounds with excellent bioactive properties, especially its biomass and carotenoid extract. S. obliquus can be explored as an alternative natural supplement to reduce risk factors or prevent disorders associated with cellular tissue integrity. Furthermore, the determination of bioaccessibility showed that the nature of the product has a significant influence on microalgae carotenoids and can help formulate foods and functional products from microalgae ingredients.